2009
DOI: 10.1124/jpet.108.149773
|View full text |Cite
|
Sign up to set email alerts
|

Arbaclofen Placarbil, a Novel R-Baclofen Prodrug: Improved Absorption, Distribution, Metabolism, and Elimination Properties Compared with R-Baclofen

Abstract: Baclofen is a racemic GABA B receptor agonist that has a number of significant pharmacokinetic limitations, including a narrow window of absorption in the upper small intestine and rapid clearance from the blood. Arbaclofen placarbil is a novel transported prodrug of the pharmacologically active R-isomer of baclofen designed to be absorbed throughout the intestine by both passive and active mechanisms via the monocarboxylate type 1 transporter. Arbaclofen placarbil is rapidly converted to R-baclofen in human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…This in turn may lead to potentially improved efficacy through a combination of greater duration of action, subject's convenience, and better safety profile compared with baclofen. 33,34 A recent study demonstrated that arbaclofen significantly reduced the total number of reflux episodes over 12 h in 44 patients with GERD. 34 The most efficacious dose of arbaclofen (60 mg) significantly reduced acid reflux episodes by 35% and heartburn episodes associated with reflux by 49%.…”
Section: Transient Lower Esophageal Sphincter Relaxation (Tlesr) Redumentioning
confidence: 99%
“…This in turn may lead to potentially improved efficacy through a combination of greater duration of action, subject's convenience, and better safety profile compared with baclofen. 33,34 A recent study demonstrated that arbaclofen significantly reduced the total number of reflux episodes over 12 h in 44 patients with GERD. 34 The most efficacious dose of arbaclofen (60 mg) significantly reduced acid reflux episodes by 35% and heartburn episodes associated with reflux by 49%.…”
Section: Transient Lower Esophageal Sphincter Relaxation (Tlesr) Redumentioning
confidence: 99%
“…7 In preclinical studies, AP produced dose-proportional exposure to R-baclofen following oral dosing, with limited systemic exposure to intact prodrug. 7 Compared with immediate-release baclofen, AP has a flatter pharmacokinetic profile and more sustained plasma levels allowing less frequent dosing and improved patient convenience.…”
Section: Introductionmentioning
confidence: 99%
“…7 In preclinical studies, AP produced dose-proportional exposure to R-baclofen following oral dosing, with limited systemic exposure to intact prodrug. 7 Compared with immediate-release baclofen, AP has a flatter pharmacokinetic profile and more sustained plasma levels allowing less frequent dosing and improved patient convenience. After single 20-mg oral doses of a prototype extendedrelease formulation of AP (SR1) in 10 healthy human volunteers, the time to maximal R-baclofen blood concentration (T max ) was 5.05 h under fed conditions (unpublished data on file at XenoPort Inc.), which is longer than the comparable mean T max of 1.9 h after administration of racemic baclofen in a separate study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations